Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2012
DOI: 10.1007/s12098-012-0767-z
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular Disease Risk Factors: A Childhood Perspective

Abstract: Atherosclerotic cardiovascular disease (CVD) is one of the leading causes of death and disability worldwide including in developing countries like India. Indians are known to be predisposed to CVD, which occur almost a decade earlier in them. Though these diseases manifest in the middle age and beyond, it is now clear that the roots of CVD lie in childhood and adolescence. Many of the conventional risk factors of CVD such as high blood pressure, dyslipidemia, tobacco use, unhealthy diet and obesity have their … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
17
0
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 52 publications
0
17
0
4
Order By: Relevance
“…The literature is increasingly supportive of childhood origins for a number of chronic diseases. It has been found that atherosclerotic development is initiated in childhood, long before clinical presentation ( 2 , 3 ) , and studies have previously linked childhood obesity with CVD in adulthood ( 4 ) . However, some evidence is less supportive ( 5 ) and a recent systematic review concluded that childhood obesity could not be used as an independent predictor for CVD risk ( 6 ) .…”
mentioning
confidence: 99%
“…The literature is increasingly supportive of childhood origins for a number of chronic diseases. It has been found that atherosclerotic development is initiated in childhood, long before clinical presentation ( 2 , 3 ) , and studies have previously linked childhood obesity with CVD in adulthood ( 4 ) . However, some evidence is less supportive ( 5 ) and a recent systematic review concluded that childhood obesity could not be used as an independent predictor for CVD risk ( 6 ) .…”
mentioning
confidence: 99%
“…Among urban Indians, exposure to multiple risk factors of CVD was evidenced during adolescence and dramatically increased by 30–39 years of age [23]. Among Indian school children, high prevalence of overweight (14.4%), obesity (2.8%), sustained high blood pressure [24, 25], coupled with maternal and fetal under-nutrition were suspected to increase the future risk of CVDs [13]. …”
Section: Introductionmentioning
confidence: 99%
“…[8] Sonuçta obezitenin önemli bir risk faktörü olduğu hipertansiyon, koroner kalp hastalıkları, diyabet gibi birçok kronik hastalık açısından yetişkinler kadar, çocuklar da önemli risk altındadır. [9,11] Günümüzde endüstriyel gelişime paralel olarak şehir yaşamının artmış olması, çalışan ebeveyn sayısındaki artış; yaşam tarzımızın değişmesine ve besinlerde kullanılan ve obeziteye zemin hazırlayan endüstriyel maddelerin ve tüketime hazır ürünlerin öğünlerimizde daha fazla yer almasına yol açmıştır. Bu konudaki reklamların etkisi, hazır yiyecek ürün-lerinin daha kolay ulaşılabilirliği ve daha ucuz olmasının da katkısı büyüktür.…”
unclassified